Memahami Peran Komunikasi Orang Tua-Guru pada Motivasi Siswa SD - Ramadhani, Ananda; Nisa, Sahrun (Lembaga Yasin AlSys, 2024)
The role of communication between parents and teachers in enhancing student motivation in elementary schools is crucial. Referring to various studies conducted by experts, it is found that strong and regular communication between parents and teachers has a positive impact on strengthening collaborative relationships, facilitating the exchange of relevant information, and helping to solve emerging problems. Additionally, a good partnership between parents and teachers can influence students' perceptions of learning and assist in better understanding the individual needs of students. Therefore, it is important for educators to recognize the significance of parent-teacher communication, overcome potential barriers, and build positive relationships with parents to support the optimal development of students in elementary schools.